2016
DOI: 10.1038/ncomms12473
|View full text |Cite
|
Sign up to set email alerts
|

A keystone mutualism underpins resilience of a coastal ecosystem to drought

Abstract: Droughts are increasing in severity and frequency, yet the mechanisms that strengthen ecosystem resilience to this stress remain poorly understood. Here, we test whether positive interactions in the form of a mutualism between mussels and dominant cordgrass in salt marshes enhance ecosystem resistance to and recovery from drought. Surveys spanning 250 km of southeastern US coastline reveal spatially dispersed mussel mounds increased cordgrass survival during severe drought by 5- to 25-times. Surveys and mussel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 32 publications
5
119
0
Order By: Relevance
“…For example, in low‐energy saltmarsh locations were sulphide stress poses a major threat to new transplants, a design including mussels and cordgrass may be most efficient. The mutualism alleviates this stress, and allows for transplanting cordgrass in widely spaced arrays, thereby maximizing the contribution of these patches to mudflat re‐colonization via clonal expansion (Angelini et al., ). However, in more hydrodynamically active locations, a clumped design, which is more effective in attenuating waves and currents than widely spaced arrays (Silliman et al., ), may yield high success rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in low‐energy saltmarsh locations were sulphide stress poses a major threat to new transplants, a design including mussels and cordgrass may be most efficient. The mutualism alleviates this stress, and allows for transplanting cordgrass in widely spaced arrays, thereby maximizing the contribution of these patches to mudflat re‐colonization via clonal expansion (Angelini et al., ). However, in more hydrodynamically active locations, a clumped design, which is more effective in attenuating waves and currents than widely spaced arrays (Silliman et al., ), may yield high success rates.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent survey among restoration agencies in the United States revealed that only 1 of 25 was implementing designs that could harness intraspecific facilitation . In a similar survey of 20 US restoration agencies conducted for this study, we found that 85% of the surveyed practitioners do not currently include positive interspecific interactions in saltmarsh restorations (Appendix S1), despite clear indications that these interactions may yield high benefits for restoration success (Angelini et al, 2015(Angelini et al, , 2016.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Empirical research in coastal ecosystems over recent decades, however, has shown that biotic interactions such as predation, competition, and, more recently, positive species interactions are also important controls, especially under high physical stress scenarios [37][38][39][40]. In particular, recent small-scale, experimental tests in marsh restoration have demonstrated that incorporating indirect positive interactions among transplants and between foundation species can increase ecosystem recovery and resilience [41,42]. These results indicate that expanding restoration designs to also consider trophic controls and indirect species interactions in addition to the physical template may enhance restoration efficacy and yield [41,43].…”
Section: Introductionmentioning
confidence: 99%